The acute effects of insect vs. beef-derived protein on postprandial plasma aminoacidemia, appetite hormones, appetite sensations, and energy intake in healthy young men - Dai, Jiaying; Lov, Jamie; Martin-Arrowsmith, Patrick W.; Gritsas, Ari; Churchward-Venne, Tyler A. (European journal of clinical nutrition, 2022)
Background/Objectives The purpose of this study was to evaluate the acute effects of ingesting beef- and insect-derived protein on postprandial plasma amino acid and appetite hormone concentrations, appetite sensations, and ad libitum energy intake. Subjects/Methods In a randomized, double-blind, crossover study, 20 young men (23 (SD: 4) y) completed two trials during which arterialized blood samples and VAS questionnaires were collected at baseline, and over 300-min after ingestion of beverages with similar energy and macronutrient content containing 25 g beef- or insect-derived (cricket) protein. Blood samples were analyzed for plasma amino acid and appetite hormone concentrations, while VAS questionnaires were applied to assess appetite sensations. After each trial, an ad libitum meal was immediately provided to assess energy intake. Results Adjusted mean postprandial incremental area under the curve (iAUC) was greater for cricket vs. beef-derived protein for plasma leucine, branched-chain amino acid, and essential amino acid concentrations (all P < 0.0001). Adjusted mean postprandial iAUC for hunger was lower following beef (−3030 (SE: 860)) vs. cricket-derived (−1197 (SE: 525)) protein (Difference: −1833 (95% CI: −3358, −308); P = 0.02), but was not different for other appetite sensations or appetite hormones (all P > 0.05). Adjusted mean ad libitum energy intake was 4072 (SE: 292) and 4408 (SE: 316) kJ following beef- and cricket-derived protein (Difference: −336 (95% CI: −992, 320); P = 0.30). Conclusion Acute ingestion of cricket and beef-derived protein leads to differences in postprandial plasma amino acid concentrations, but elicits similar effects on appetite hormones, appetite sensations, and ad libitum energy intake in young men.